THE PERSPECTIVES OF ECONOMIC DEVELOPMENT IN NEW UZBEKISTAN - Ubaydullaeva Oydinoy Xabibullayevna (Web of Journals Publishing, 2024)
The article examines key aspects and trends in the development of the economy of Uzbekistan in the context of reforms being carried out within the framework of the "New Uzbekistan" concept. The main focus is on economic transformations aimed at diversifying industries, supporting entrepreneurship, attracting investments and improving the well-being of the population. Strategic directions of economic policy, including the role of innovation, digitalization and international cooperation, are analyzed. The work provides a theoretical overview of the prospects for sustainable economic growth and the tasks facing the country's economy in the coming years.
Keywords: Economy, New Uzbekistan, reforms, investments, diversification, innovation, digitalization, sustainable growth.